Rebel power! - Nesworthy, Lauren (London : Dorling Kindersley, 2015)
Discover all there is to know about the heroes from the planet Lothal, including Ezra, Hera and Chopper! Read all about the Rebels latest adventures as they grow in strength, upping their fight against the Empire.
"Disney"--Cover.
Includes index.